Innovation as Guided Coevolution: The Trend Micro Case (1998 – 2005) - Kuo, Anthony; Lo, Tsih-tse; Sutthiphisal, Dhanoos; Chiu, Ivy (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2020)
Innovation is considered crucial for firms to compete effectively. The extant research on innovation has provided significant insights, but, however, the majority examined innovation in the context of technology. Only a few exceptions have explored how social and behavioral factors influence firms in the innovation processes. Based on the coevolution perspective, this study examines innovation process of a software firm participating in the ever-changing information security software industry. We focused on how the firm guided its offerings to coevolve with new technologies and relevant changes among different groups of human actors. Our data reveals that the firm developed different offerings in different periods to cope with the changing driving forces—technologies, users, and hackers—in each period. Effectively identifying the driving forces and guided its offerings to coevolve with them, the firm successfully sustained its competitive advantage in the period characterized with turbulence in the environment.Keywords: innovation, coevolution, software, high-tech